Measuring Stony Coral Tissue Loss Disease Induction and Lesion Progression Within Two Intermediately Susceptible Species, Montastraea cavernosa and Orbicella faveolata - Eaton, Katherine R.; Landsberg, Jan H.; Kiryu, Yasunari; Peters, Esther C.; Muller, Erinn M. (Frontiers in Marine Science, 2021)
During the last several decades, Florida’s Coral Reef (FCR) has been impacted by both global and local stressors that have devastated much of its living coral cover. Additionally, since 2014 FCR has experienced a lethal disease outbreak termed stony coral tissue loss disease (SCTLD). Here, we examined SCTLD spreading dynamics within and among fragmented coral colonies and quantified lesion progression rate of two intermediately susceptible species—Montastraea cavernosa and Orbicella faveolata—through induction experiments conducted in laboratory aquaria. Montastraea cavernosa colonies showing subacute tissue loss were sequentially fragmented parallel to the lesion edge to determine whether isolated tissue that showed no tissue-loss signs, referred to as isolated apparently healthy (AH) donor fragments, would subsequently exhibit tissue loss. Additionally, AH M. cavernosa and O. faveolata fragments, referred to as recipient fragments, were placed in direct contact with the M. cavernosa donor fragments to assess incidence of new tissue-loss lesions. Finally, AH M. cavernosa donor fragments were placed in direct contact with recipient M. cavernosa and O. faveolata fragments to account for aggression from direct contact. Samples were collected for histopathology of the corals through time. Many isolated AH donor fragments developed tissue-loss lesions during the 60-day study, suggesting SCTLD may be systemic within small-sized colonies. Our results confirmed that physical contact between recipient fragments and subacute SCTLD-lesioned tissue often led to tissue loss in recipient fragments. None of the control recipient or donor fragments experienced tissue loss. Grossly, multifocal lesions started on or adjacent to the septal and costal basal body walls with tissue loss progressing across the polyp septa and coenenchyme, respectively, in both species. Histologically, initial tissue-loss lesions in both species exhibited characteristic lytic necrosis (LN) at the basal body wall of the gastrodermis. Orbicella faveolata exhibited higher rates of lesion appearance and subsequent mortality compared to M. cavernosa, but once a lesion appeared, M. cavernosa lost tissue faster than O. faveolata. This work contributes to the growing knowledge of SCTLD dynamics and highlights the differences in lesion progression within susceptible species.